"Exercise Is Medicine": Curbing the Burden of Chronic Disease and Physical Inactivity. (March 2015) - Coombes, Jeff S.; Law, Jen; Lancashire, Bill; Fassett, Robert G.
An exercise program designed to improve fitness is essential for most adults. Exercise decreases the risk of cardiovascular disease, type 2 diabetes, some cancers, depression, and anxiety. Most fail to achieve recommended exercise levels. Only 1.3% of Australian general practice (GP) consultations provide exercise counseling and advice. Australia provides Medicare reimbursement for consultations with Accredited Exercise Physiologists through allied health care plans initiated through primary care. Exercise Is Medicine is an initiative to equip primary care providers with resources, education, and strategies to increase physical activity and reduce sedentary behavior. The objective of Exercise Is Medicine is to improve the health and well-being of our nation. We describe Exercise Is Medicine and encourage primary care providers to discuss physical activity and exercise with their patients and provide them with resources to encourage this activity and referral pathways to train exercise professionals. This will assist primary care providers in treating their patients.